Legal regulation of the application of economic mechanisms for ensuring the rational use of natural resources: the experience of foreign countries - Легеза, Юлія Олександрівна; Легеза, Ю. О.; Легеза, Юлия Александровна; Leheza, Yuliia O.; Сурілова, Олена Олексіївна; Сурілова, О. О.; Сурилова, Елена Алексеевна; Surilova, Olena O. (Baltija Publishing, 2019)
The purpose of the study is to determine the most optimal ways to solve the problems of financing the implementation of environmental protection measures formulated based on the positive experience of foreign countries in the field of ensuring the rational use of natural resources. Methodology. The method of comparative legal research was used to analyse foreign experience in the application of economic mechanisms for ensuring the rational use of natural resources, and the methods of modelling, analysis, and synthesis allowed determining the directions of increasing the efficiency of economic incentive use in Ukraine. Research results. Based on the studied experience of legal regulation of the application of economic mechanisms for ensuring the rational use of natural resources in the countries of the European Union, the United States of America, Great Britain, Canada, and other foreign countries, it was concluded on the expediency of its implementation in Ukraine. The author determined the appropriateness of the introduction of tax privileges of economic activity of entities that promote the use of advanced technologies, which contribute to reducing the negative impact on the environment. The expediency of application in Ukraine of an extensive system of taxation of activities associated with the use of natural resources by means of activating the introduction of direct taxes paid directly by natural users is substantiated. The practicability of inclusion of payments for obtaining appropriate special permits (licenses), which are granted not only for the use of natural resources but also for the activities related to environmental pollution, in the system of economic mechanisms for ensuring the rational use of natural resources is substantiated. The practical importance of the study. The expediency of introducing in Ukraine the approach of financial substantiation of national and regional programs in the sphere of natural resources utilization, which are realized at the expense of state and local budgets and successfully applied in foreign countries, is proved. The originality of the research. The results and conclusions of th e research can be used in the process of improving the legal regulation of the application of economic mechanisms for ensuring the rational use of natural resources.

Метою дослідження є визначення найбільш оптимальних шляхів вирішення проблем фінансування реалізації природоохоронних заходів, сформульованих на основі позитивного досвіду зарубіжних країн у сфері забезпечення раціонального використання природних ресурсів. Методологія. Методом порівняльно-правового дослідження було проаналізовано зарубіжний досвід застосування економічних механізмів забезпечення раціонального використання природних ресурсів, а методи моделювання, аналізу та синтезу дозволили визначити напрями підвищення ефективності використання економічного стимулювання в Україні. Результати дослідження. На основі вивченого досвіду правового регулювання застосування економічних механізмів забезпечення раціонального використання природних ресурсів у країнах Європейського Союзу, Сполучених Штатах Америки, Великобританії, Канади та інших зарубіжних держав зроблено висновок на доцільність його впровадження в Україні. Автором визначено доцільність запровадження податкових пільг господарської діяльності суб’єктів, які сприяють використанню прогресивних технологій, що сприяють зменшенню негативного впливу на навколишнє середовище. Обґрунтовано доцільність застосування в Україні розгалуженої системи оподаткування діяльності, пов’язаної з використанням природних ресурсів, шляхом активізації запровадження прямих податків, що сплачуються безпосередньо природними користувачами. Доцільність включення до системи економічних механізмів забезпечення раціонального використання природних ресурсів платежів за отримання відповідних спеціальних дозволів (ліцензій), які надаються не лише на використання природних ресурсів, а й на діяльність, пов’язану із забрудненням навколишнього середовища. є обґрунтованим. Практичне значення дослідження. Доведено доцільність запровадження в Україні підходу фінансового обґрунтування загальнодержавних та регіональних програм у сфері використання природних ресурсів, які реалізуються за рахунок державного та місцевих бюджетів і успішно застосовуються в зарубіжних країнах. Оригінальність дослідження. Результати та висновки дослідження можуть бути використані в процесі вдосконалення правового регулювання застосування економічних механізмів забезпечення раціонального використання природних ресурсів.
Leheza Yu. Legal regulation of the application of economic mechanisms for ensuring the rational use of natural resources: the experience of foreign countries / Yu. Leheza, O. Surilova // Baltic Journal of Economic Studies. – Vol. 5. - № 3. - Baltija Publishing, 2019. – P. 99-103.
Keywords: administrative act; use of natural resources; permit; environmental tax; economic mechanism; license; адміністративний акт; використання природних ресурсів; дозвіл; екологічний податок; господарський механізм; ліцензія; Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::SOCIAL SCIENCES::Business and economics